Goods Deposit Agreement In The Civil Code and KHES - Oriza Trisina Br. Sitepu; Adinda Rida Cahyani; Dinda Andini; Raisha Zahra Amanda; Mohammad Amir Bin Wan Harun (ISNU Sumatera Utara, 2025)
This study examines in depth the concept of the goods deposit agreement (wadi'ah) regulated in two legal systems in Indonesia, namely the Civil Code (KUH Perdata) and the Compilation of Sharia Economic Law (KHES). Using qualitative research methods and a normative juridical approach, this study aims to analyze the similarities and differences in the provisions of goods deposit in the two legal systems, as well as their implications for the practice of goods deposit in society. Data collection was conducted through a literature study by analyzing primary, secondary, and tertiary legal sources. The results of the study indicate that although both legal systems regulate goods deposit, there are fundamental differences in their concept and implementation. The Civil Code views goods deposit as a mutual agreement and can be accompanied by wages, while KHES regulates it in the context of a wadi'ah contract based on sharia principles. This study also reveals that KHES provides more comprehensive regulations regarding the rights and obligations of the parties, as well as the legal consequences arising from goods deposit agreements. This finding provides an important contribution to the development of the legal system in Indonesia, particularly in the harmonization of conventional law and Islamic economic law.